2022-RA-1133-ESGO Utility values in PROC. (20th October 2022) - Mehra, Anupriya; Indukuri, Nikhila; Musat, Mihaela; Chavez, Gordon; Proescholdt, Christina
Abstract : Introduction/Background: Platinum-resistant ovarian cancer (PROC) is associated with a substantial humanistic and economic burden due to disease symptoms, treatment-related side effects and costs. Cost-utility analyses that inform healthcare decision-makers require a set of health state utility values (HSUVs). As part of a systematic literature review (SLR), published evidence of HSUVs associated with PROC were described. Methodology: The scope of the SLR was defined using the Patient population, Intervention, Comparators, Outcomes measures and Study design (PICOS) statement, and performed using pre-defined search terms in accordance with PRISMA guidelines. Key biomedical literature databases (Medical Literature Analysis and Retrieval System Online [MEDLINE®] and Excerpta Medica Database [Embase®]), EconLit and Cochrane were searched for records dated up to July 6, 2021. Relevant congresses (2017–2021), previous health technology assessment submissions, and previously conducted SLRs were also searched to capture relevant data. Results: Out of 34 studies from the SLR, 17 publications reporting HSUVs were identified. Of these, nine studies gathered EQ-5D values directly from ovarian cancer patients, four mapped EQ-5D HSUVs from FACT-O or FACT-G values, three studies mapped utility values from other solid tumor indications and one modeled EQ-5D HSUVs using Bayesian regression from patient registry data. HSUVs were relatively high at pre-progression (range 0.610 to 0.718) while patients are receiving routine chemotherapy, with a lower value for those experiencing grades 3 and 4 toxicity (0.500). HSUVs increased in those receiving maintenance therapy with PARP inhibitors after chemotherapy (range: 0.710 to 0.838). There was a decrease observed those progressed on platinum chemotherapy (range 0.40 to 0.649), with a median disutility from pre- to post-progression of 0.093. Conclusion: HSUVs for each line of therapy showed considerable heterogeneity, likely due to variability of data sources and differences in patient populations. Careful deliberation should be taken when conducting cost-utility analyses in patients with ovarian cancer.